PENGARUH KUNJUNGAN WISATAWAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BANDA ACEH TAHUN 2012 - 2015 - Yushita Marini (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Banda Aceh is one of the city of Islamic tourism in Indonesia, therefore it is expected that regional income can be obtained from tourism income. As a source of revenue of income, tourism is influenced by tourist visits. This study aims to determine whether there is influence between the visiting of the domestic tourists and the foreign tourists to the regional revenue in the city of Banda Aceh. This research uses quantitative approach and data analysis used is simple regression analysis. The source of this research is taken from the Banda Aceh Statistics Data Report 2012 to 2015. The results show that there is influence between the visit of tourists to the city's original revenue of Banda Aceh, this is indicated by the increase of the number of tourists to increase the original income of the regional.